Assessing financial capability among people with disabilities in India: applying Sherraden’s framework - Arora, Himanshu (Journal of Social Review and Development, 2025)
Financial well-being is a fundamental determinant of quality of life, yet people with disabilities (PWDs) in India face systemic barriers that significantly restrict their economic inclusion, financial literacy, and access to formal financial services. These barriers increase vulnerability to poverty and social exclusion in the Indian context, despite the government’s efforts such as the Pradhan Mantri Jan Dhan Yojana (PMJDY) and disability rights legislation like the Rights of Persons with Disabilities (RPwD) Act, 2016. This study applied Michael Sherraden’s Financial Capability Framework to empirically examine how financial literacy (the “ability”) and financial inclusion (the “opportunity”) contribute jointly to the financial well-being and stability of PWDs in India. Using nationally representative secondary data drawn from the National Sample Survey Office (NSSO), National Centre for Financial Education (NCFE), and Reserve Bank of India (RBI) financial inclusion statistics, this research employed structural equation modelling and path analysis on a sample of approximately 2,500 adults Indian PWDs. Key findings revealed that financial literacy positively predicted financial well-being but that access to formal financial products exerts a stronger direct influence and moderates the effect of literacy, indicating that systemic access is crucial. The research highlighted disparities rooted in gender, education, rural-urban residence, and regional variation. Policy implications emphasize multi-level, disability-sensitive interventions focusing on both financial education and inclusive financial services, supported by social work practice and legal enforcement aligned with India's socio-economic context.